Mathematical Model Applied to Monitoring the Glucose-Insulin Interaction inside the Body of Diabetes Patients - Akter, Sonia; Islam, Md Sirajul; Biswas, Md Haider Ali; Mandal, Sajib (GANIT: Journal of Bangladesh Mathematical Society, 2020)
The incidence and prevalence of diabetes are increasing all over the world and complication of diabetes constitutes a burden for the individuals and whole society. In this paper, we propose a mathematical model for monitoring glucose-insulin regulatory system in the human body. The non-linear cases are considered, and the model is analysed by using Lyapunov’s method. The mathematical model, discussed the critical situation of the diabetes patients as well as for normal person are analysed for stability. The numerical approximation is used to verify the analytical results and the obtained solutions represent the complex situation of diabetes patients. GANIT J. Bangladesh Math. Soc.Vol. 40 (2020) 1-12